A review of public transport policies in remote communities in Chile - Roberto Villalobos; Marcela Mu\~noz; Natalia Berríos; Eduardo Koffman (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2021)
This report looks at the policies and programmes Chile has been putting in place over the past few decades to foster the development of public transport in remote communities. In particular, it has been taking a regional approach and encouraging private investment in transport.
Keywords: 330; Öffentlicher Verkehr; Periphere Region; Chile